Approach of management a patient with vertigo in out-patient practice: case of recurrent benign paroxysmal positional vertigo with vitamin D deficiency - A. S. Bedenko (Лечащий Врач)
Dizziness is one of the most frequent causes of appliance to neurologist. The occurrence of dizziness increases in elder groups. The first goal of a neurologist is the differentiation between central and peripherial vertigo. It is necessary for second stage to make detalized differential diagnosis. To realize this purpose doctor should carry out neurovestibular investigation, including HINT test, shaking-test,test Fukuda and mandatory performing of positional tests. The further management includes adequate vertigolytic therapy, treatment of the basic disease and creation of a rehabilitation scheme, which includes both vestibular gymnastics and other non-drug methods (biofeedback, exercises on a stabiloplatform), and drugs that improve vestibular compensation. Peripheral vertigo is much more common than central vertigo and is the most common cause spinning vertigo is a benign paroxysmal positional vertigo. According to various estimates, up to 85% of benign paroxysmal positional vertigo cases have idiopathic origin, frequency of relapse is about 50%. The article presents a clinical case of recurrent benign paroxysmal positional vertigo with multiple canal involvement. A feature of this case is its combination with a vitamin D deficiency. Today, data have been accumulated indicating that vitamin D deficiency and insufficency is not just a comorbid condition often detected in patients with benign paroxysmal positional vertigo, but, most likely, is a factor in the development and recurrence of benign paroxysmal positional vertigo. However, the data are rather contradictory and require further investigation. Identifying and correcting of metabolic factors will optimize therapy.